An observational study on pattern of mortalities as per ICD-10 classification system in a tertiary care hospital in India - Nandi, Chinmay; Mitra, Kaushik; Bhaumik, Dipankar; Paul, Shamik Parna (Asian Journal of Medical Sciences, 2021)
Background: Records of vital events like death constitute an important component of the Health Information System. Patterns of mortality decline that occur with the demographic transition is a change in the distribution of deaths by cause away from a pattern dominated by communicable diseases toward one in which non-communicable diseases account for the overwhelming majority of deaths. Aims and Objective: To identify the mortality pattern in Burdwan Medical College as per ICD-10 classification in the year 2017.The study also evaluated socio-demographic distribution and causes of deaths during that period. Materials and Methods: It was an Institution based retrospective observational study. Complete enumeration of all hospital records of medically certified deaths of in-patients from different departments except the Paediatrics who died in 2017 was done. The underlying cause of death was classified according to I.C.D 10th revision, version 16. Information collected included also the demographic characteristics like age, gender, date of admission, place of residence and date of death for the study. Results: In this study, most of the deaths were seen in males (59.99%), with a sex ratio of female to male deaths to be 667 per thousand. The major proportion of deaths was in the age group of 55 to 64 years (23.53%). The percentage distribution of ten major cause groups of death for the period from January to December during 2017 reveals that the group “Diseases of the Circulatory System” had occupied the position of the top-most killer and it had maintained the trend throughout the year with the highest rate in the month of March (43.9%). The cause of death was more in Non-Communicable diseases (Chapter IX, Chapter XIX) compared to that of Communicable diseases. Conclusion: Procedures for death certification and coding of underlying causes of death need to be streamlined to improve reliability of registration data needed for epidemiological research or public health policy formulation.